The Impact of CO2 Emission on Output in Algeria. (August 2015) - Allali, M.; Tamali, M.; Rahli, M.
Abstract: Emissions of global warming gases continue to rise as the world burns ever more coal, oil and gas for energy. The study investigates the nexus between carbon dioxide (CO2 ) emission per capita and economic growth of energy consumption in over the period 1990-2100. To evaluate the impact of CO2 emission on relative variables, this study verifies that there are positive long-run relationship among CO2 emissions, Electric power consumption and Energy use. This paper also proves bi-directional causality between CO2 emission and electric power consumption (modeling the impact of CO2 emission on output especially in Algeria). The policy makers may evaluate exogenous effect to seeking economic growth for global climate warming and to formulate energy policies.